Traditional ecological knowledge and flood risk management: A preliminary case study of the Rwenzori - Bosco Bwambale; Moses Muhumuza; Martine Nyeko (Jàmbá, 2018)
The shift from flood protection to flood risk management, together with recent arguments on incorporating culture in managing risk, underscores the application of traditional ecological knowledge (TEK) in managing disasters from flood hazards. Yet, documentation and incorporation of TEK into practice remains a challenge. This article contributes to addressing this challenge by exploring the existence of TEK to flooding in the Rwenzori Mountains, Uganda. Using semi-structured interviews, data were collected from residents of the Nyamwamba watershed where intense flash floods caused deadly impacts in May 2013. Collected data were analysed using content, thematic and interpretive analysis techniques. Results indicate that TEK is exhibited through various traditional ecological approaches (TEAs). Although endangered, TEAs (conducted through collective action for a communally accepted end) are framed in three main activities: (1) assessment and prediction of rainfall and flood by the traditional hydro-meteorologist (diviner) and the traditional rain forecaster (rainmaker); (2) the mountain cleansing ritual (which act as flood risk awareness platform); and (3) immunising riverine communities through planting certain indigenous plants, which improve hydrological systems through their high conservation value for native ecological diversity. As most TEAs are conducted through collective action, they represent a platform to understand local capacities and enhance adoption of measures, and/or a source of knowledge for new measures to address flood risk. Therefore, full-scale investigations of these TEAs, determining how relevant TEAs are fine-tuned, and (scientific) measures enculturated based on fine-tuned TEAs could result in effective flood risk management in various flood hotspots where TEAs influence action.